From ideal to real: a qualitative study of the implementation of in situ interprofessional simulation-based education - Mindy Ju; Naike Bochatay; Kathryn Robertson; James Frank; Bridget O’Brien; Sandrijn van Schaik (BMC Medical Education, 2022)
Abstract Background Despite the widespread adoption of interprofessional simulation-based education (IPSE) in healthcare as a means to optimize interprofessional teamwork, data suggest that IPSE may not achieve these intended goals due to a gap between the ideals and the realities of implementation. Methods We conducted a qualitative case study that used the framework method to understand what and how core principles from guidelines for interprofessional education (IPE) and simulation-based education (SBE) were implemented in existing in situ IPSE programs. We observed simulation sessions and interviewed facilitators and directors at seven programs. Results We found considerable variability in how IPSE programs apply and implement core principles derived from IPE and SBE guidelines with some principles applied by most programs (e.g., “active learning”, “psychological safety”, “feedback during debriefing”) and others rarely applied (e.g., “interprofessional competency-based assessment”, “repeated and distributed practice”). Through interviews we identified that buy-in, resources, lack of outcome measures, and power discrepancies influenced the extent to which principles were applied. Conclusions To achieve IPSE’s intended goals of optimizing interprofessional teamwork, programs should transition from designing for the ideal of IPSE to realities of IPSE implementation.